Uso de antioxidantes em diluentes de criopreservação de sêmen bovino - Silva, Natalia do Carmo (2017)
The objective of this study was to evaluate the addition of antioxidants in different cryopreservation diluents on bovine semen quality after thawing and the in vitro production of embryos. First, the effects of adding different concentrations of glutathione (1.5 and 2.5 mM) and melatonin (0.5 and 1.0 mM) in egg yolk semen cryopreservation diluents (Bovimix®) and soy lecithin (Andromed®) were evaluated. The results showed that the addition of the antioxidant glutathione did not improve the maintenance of sperm characteristics of bovine semen. Melatonin had a negative effect on the spermatic parameters evaluated. The diluent Andromed® obtained better parameters of spermatic kinetics when compared with the diluent Bovimix®. However, in relation to the membrane integrity analyzes of the Bovimix® diluent showed better performance in the maintenance of these parameters. The effect of the cryopreservation diluents and the addition of glutathione in the vitro production of bovine embryos (PIVE) was then evaluated. The rate of cleavage, blastocyst rate and hatching were evaluated eight and nine days after IVF, as well as the correlation between sperm characteristics and PIVE. The diluent Andromed® provided a better cleavage rate, with no effect of the addition of glutathione in it. However, the addition of 2.5 mM glutathione in the Bovimix® diluent improved the cleavage rate. There was a significant correlation of high and low magnitude between some sperm characteristics with the rate of cleavage. It was concluded that glutathione did not improve sperm viability. Melatonin worsened the maintenance of sperm characteristics. Andromed® diluent was more efficient in the in vitro production of bovine embryos with no glutathione effect observed in this diluent. The addition of 2.5 mM glutathione in the egg yolk Bovimix® diluent gave a higher cleavage rate. In vitro evaluation of semen quality is not the best method to predict the fertilizer potential of the same in PIVE, because only significant low to moderate magnitude correlations were observed between some parameters of semen quality and fertilization rate.